A Fitting Agenda for Arctic's Next Forty Years - Berger, Thomas R. (ARCTIC, 1987)
. The ambitions of all of the circumpolar powers - Canada, the U.S., the Soviet Union, the Scandinavian countries - converge in the Arctic. Their activities, now and in the future, threaten the arctic environment. Offshore drilling in arctic waters, diversion of arctic rivers, accumulation of arctic haze can offer enormous risks to arctic marine life and weather systems. . A concept of collective stewardship must be developed if we are to ensure the protection of the arctic environment. The Reagan administration's determination to open up the calving grounds of the Porcupine caribou herd along the arctic coast of Alaska to oil and gas exploration and production threatens the future of a herd that is an international environmental resource and threatens as well the future of Inuit and Dene villages on both sides of the international boundary. The pursuit of one nation's goals can cause social and environmental havoc. Let's not permit the debate about the Arctic to be cast in terms of sovereignty, of national ambition. We should not allow the sterile goals of the nation-state to define the future of the Arctic. National sovereignty is a limited and limiting concept. Sovereignty is a national issue, stewardship an international issue. Beyond sovereignty comes the concept of stewardship by all of the circumpolar powers over the circumpolar basin. In the Arctic an attempt ought even to be made to transcend the particularities of the Cold War. It is in the Arctic that the survival of the Native subsistence economy is essential; it is there that the place of Native peoples within our polities will be determined; it is there that our commitment to environmental goals and international cooperation will be tested: a fitting agenda for Arctic's next 40 years.